A case of misalignment: the perspectives of local and national decision-makers on the implementation of psychological treatment by telephone in the Improving Access to Psychological Therapies Service - Kelly Rushton; Claire Fraser; Judith Gellatly; Helen Brooks; Peter Bower; Christopher J. Armitage; Cintia Faija; Charlotte Welsh; Penny Bee (BMC, 2019)
Abstract Background Psychological treatment delivered by telephone is recommended by the National Institute for Health and Care Excellence (NICE) for mild to moderate depression and anxiety, and forms a key part of the Improving Access to Psychological Therapy (IAPT) programme in the UK. Despite evidence of clinical effectiveness, patient engagement is often not maintained and psychological wellbeing practitioners (PWPs) report lacking confidence and training to deliver treatment by telephone. This study aimed to explore the perspectives of professional decision makers (both local and national) on the barriers and facilitators to the implementation of telephone treatment in IAPT. Methods Sixteen semi-structured qualitative telephone interviews and one focus group were carried out with decision makers (n = 21) who were involved locally and nationally in policy, practice and research. The interviews and focus group were coded thematically, and then mapped onto the four core constructs of Normalisation Process Theory (NPT). Results The use of telephone for psychological treatment was universally recognised amongst participants as beneficial for improving patient choice and access to treatment. However, at service level, motives for the implementation of telephone treatments are often misaligned with national objectives. Pressure to meet performance targets has become a key driver for the use of telephone treatment, with promises of increased efficiency and cost savings. These service-focussed objectives challenge the integration of telephone treatments, and PWP acceptance of telephone treatments as non-inferior to face-to-face. Ambivalence among a workforce often lacking the confidence to deliver telephone treatments leads to reluctance among PWPs to 'sell' treatments to a patient population who are not generally expecting treatment in this form. Conclusions Perceptions of a need to 'sell' telephone treatment in IAPT persist from top-level decision makers down to frontline practitioners, despite their conflicting motives for the use of telephone. The need for advocacy to highlight the clinical benefit of telephone treatment, along with adequate workforce support and guidance on best practice for implementation is critical to the ongoing success and sustainability of telephone treatment in primary care mental health programmes.